1996
DOI: 10.1007/bf02246645
|View full text |Cite
|
Sign up to set email alerts
|

Increased 5-HT2C receptor responsiveness occurs on rearing rats in social isolation

Abstract: To investigate whether isolation rearing alters 5-hydroxytryptamine2C (5-HT2C) receptors, the effect of the serotonin agonist m-chlorophenylpiperazine (mCPP) was examined on elevated plus-maze behaviour, plasma corticosterone and brain 5-HT2C receptor protein levels in rats. There was no distinction between behaviour or corticosterone levels in drug-free isolates or socially housed rats exposed to the elevated plus-maze. The anxiogenic response to mCPP (decrease in open arm entry and time and an increase in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 28 publications
6
51
0
Order By: Relevance
“…Furthermore, animals reared in isolation have increased sensitivity to 5-HT 2C agonists (Fone et al, 1996), confirming in another model of depression the importance of 5-HT 2C receptor sensitivity. Patients with depression exhibit abnormal circadian rhythms of plasma cortisol, with a prolonged peak and early timing of the nadir, although a transient (or elevated) nadir usually occurs (Linkowski et al, 1987).…”
Section: -Ht 2c Receptorssupporting
confidence: 55%
“…Furthermore, animals reared in isolation have increased sensitivity to 5-HT 2C agonists (Fone et al, 1996), confirming in another model of depression the importance of 5-HT 2C receptor sensitivity. Patients with depression exhibit abnormal circadian rhythms of plasma cortisol, with a prolonged peak and early timing of the nadir, although a transient (or elevated) nadir usually occurs (Linkowski et al, 1987).…”
Section: -Ht 2c Receptorssupporting
confidence: 55%
“…Animals exposed to prior stress exhibit an enhanced, reduced or equivalent hypothalamic-pituitary-adrenal response to a subsequent acute stressor (5-7). Social isolation produced by individual housing affects brain monoamine and adrenal gland functions in experimental animals (8)(9)(10)(11). Social isolation and acute environmental changes are risk factors in human depression, and represent a lack of the social stimuli necessary to modulate adaptive responses to new situations (12).…”
Section: Introductionmentioning
confidence: 99%
“…Manipulations of 5-HT receptors with various agonists and antagonists have revealed that social isolation in rodents differentially affects 5-HT receptor subtypes (Wright et al, 1991;White et al, 1991;Sanchez et al, 1993;Fone et al, 1996). Binding studies show transient down-regulation of presynaptic 5-HT 1A receptors in the midbrain of mice isolated for 3-6 weeks (Rilke et al, 1998).…”
Section: -Ht and Extrinsic Factors That Affect Aggressionmentioning
confidence: 99%